Efektifitas Pemberian Terapi Accupressure Titik Pericardium 6 Dalam Membantu Menurunkan Mual Dan Muntah Pada Ibu Hamil Trimester 1 Di Klinik Utama Permata Ibu Kec. Kumai Kab. Kotawaringin Barat - Suprapti, Dwi (Sahabat Publikasi Kuu, 2024)
A feeling of discomfort in the back of the throat or stomach known as nausea can lead to vomiting (SDKI DPP PPNI Working Group Team, 2016). During the first trimester, pregnant women frequently experience nausea and vomiting, which is also known as morning sickness. One of the symptoms of the discomforts that can occur in every pregnancy. Pregnant women's complaints of nausea and vomiting can be reduced by giving accupressure massage at the Pericardium 6 meridian point (PC 6), so that the duration of the accupressure massage at the PC 6 point is effective for 10 minutes or more with a pressure force of 1/3 of the nail until it turns white with a frequency of four times a day has been proven to be effective in reducing nausea and vomiting in pregnant women in the first trimester. The research method used in this study was pre-experimental design with a one group pre-post test approach, the number of respondents was 11 pregnant women. Data collection used the Pregnancy Unique Quantification of Emesis and Nausea (PUQE) questionnaire. Data analysis in this study was descriptive analytical. The results showed that before accupressure massage was given at the Pericardium meridian point (PC 6) how bad the nausea and vomiting are was in the moderate category Score (7-12) in 5 cases (45.50%), and in the severe category 4 people (36.3%), After acupressure was carried out at the PC 6 meridian point, how bad the nausea and vomiting are moderate category (score 7-12) fell to 2 women (18%), the severe category to 2 people (18%), and the mild category to 7 people (64%) . Conclusion: Acupressure at the Neiguan point is effective in reducing complaints of nausea and vomiting in first trimester pregnant women.